2015
DOI: 10.1007/978-3-319-15630-9_8
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxykynurenic Acid and Type 2 Diabetes: Implications for Aging, Obesity, Depression, Parkinson’s Disease, and Schizophrenia

Abstract: Aging, obesity, depression, Parkinson's and other neurodegenerative diseases, schizophrenia, and treatment with antipsychotic drugs are highly associated with insulin resistance (IR) and type 2 diabetes mellitus (T2D). Molecular mechanisms of increased associations remain uncertain. Current review of literature and our data suggest that one such mechanism is the overproduction of diabetogenic factors resulting from dysregulation of upstream and downstream pathways of tryptophan (TRP)-kynurenine (KYN) metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 181 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…The mechanisms of such association are not clear. Dysregulation of Trp-Kyn pathway in obesity was suggested [3,6] and supported by clinical and experimental data [2729]. It is noteworthy that in Drosophila HSD induces not only IR/T2D but obesity as well [11].…”
Section: Discussionmentioning
confidence: 88%
“…The mechanisms of such association are not clear. Dysregulation of Trp-Kyn pathway in obesity was suggested [3,6] and supported by clinical and experimental data [2729]. It is noteworthy that in Drosophila HSD induces not only IR/T2D but obesity as well [11].…”
Section: Discussionmentioning
confidence: 88%
“…Chronic stress or chronic low grade inflammation – induced up-regulation of upstream steps of KP combined with P5P deficiency, resulting in shifting of down-stream KYN metabolism from formation of NAD toward production of diabetogenic KYN derivatives, might contribute to increased association of IR (and T2D) with aging, neurodegenerative diseases (e.g., Parkinson’s, Alzheimer’s and Huntington’s), and schizophrenia and treatment by antipsychotic medications; viral infections (e.g., HIV and HCV), and depression [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Peripherally produced Kyn, ANA and 3-HK (but not KYNA) might contribute to central pathology by crossing blood brain barrier (BBB) [ 37 ] and entering a pool of centrally formed Kyn metabolites [ 38 ]. Dysregulation of Trp – Kyn pathway was suggested as a common signaling pathway for schizophrenia and Metabolic Syndrome in schizophrenia [ 9 , 13 , 15 ]. Elevated serum concentrations of KYNA, indicative of KMO deficiency, were observed in ZFR [ 13 ], and associated with weight gain in humans [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical studies, only elevated ANA and decreased 3-HK concentrations were observed in serum of SP without concurrent increase of Kyn and KYNA [ 15 , 31 ]. Therefore, we were interested to expand our previous study [ 9 ] by assessing serum KP metabolites in a subgroup of SP with elevated KYNA.…”
Section: Introductionmentioning
confidence: 99%